3D Heat Transfer Analysis of a Miniature Copper-Water Vapor Chamber with Wicked Pillars Array. (28th March 2013) - Jiang, Yong; Carbajal, Gerardo; Sobhan, C. B.; Li, Ji
Abstract : A three-dimensional analysis of the heat and mass transfer phenomena inside a vapor chamber is essential for correctly understanding its thermal performance limitations and structural optimization. This paper presents a complete three-dimensional numerical analysis and comparative study of two different miniature vapor chambers designs with identical external geometry and dimensions but different internal structures: one having a wicked pillar array and the other one without the wicked pillars array. The distribution of the wicked pillar array in the vapor core was aligned. Detailed comparative experimental results are also reported, which were performed to verify the calculations from the numerical simulations. It was found that the numerical and experimental results agree quite well, especially at high heat flux values. It is also observed that the vapor chamber with wicked pillars had a better thermal performance than the conventional design, with a 5% decrease in terms of total thermal resistance due to the added extra channels that allow a better flow of the working fluid to the evaporator surface. An insight into how improving the thermal performance of a vapor chamber is provided through the detailed three-dimensional numerical simulations.